Pengembangan Media Pembelajaran Berbasis Multimedia di MA Muhammadiyah 1 Malang - Nathasa Pramudita Irianti; Hasminar Rachman Fidiastuti; Antonius Alam Wicaksono (Neolectura, 2021)
This research is a development research that aims to develop multimedia-based learning media in mathematics. The material used is Three Dimensional material. After the multimedia-based learning media has been designed, content validation tests are carried out, media expert validation tests, user validation tests (teachers), and limited tests (students). The results of media expert validation showed an average score of 61.8% and was included in the appropriate criteria. The results of the material expert validation showed an average score of 80% and was included in the appropriate criteria. The user (teacher) validation test showed an average score of 91.25% and was included in the appropriate criteria. In the limited test stage (students) as many as 25 students at MA Muhammadiyah 1 Malang produced an average score of 82.01% and were included in the appropriate criteria. Based on the results of all media validation carried out, the average feasibility of this multimedia-based learning media is 78.76% and according to the eligibility criteria, this multimedia-based learning media is declared feasible and can be used by students as additional media in learning Three Dimensional material.